2018
DOI: 10.1016/j.asjsur.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Which treatment modality for pediatric pilonidal sinus: Primary repair or secondary healing?

Abstract: We did not find any significant difference concerning length of hospitalization, duration of postoperative pain and recurrence rate. However we determined that the primary repair group recovery time is significantly shorter compared to our secondary healing group. Therefore we recommended primary repair in the treatment of primary repair PS in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In research by Elsshazly et al, 20 the post‐operative pain in the LIMBERG flap procedure was significantly less than the excision and primary closure procedure groups ( P ‐value<.001). However, in separate studies by Karaks et al, 9 Ozcan et al, 5 and Berthier et al, 13 there was no significant difference between groups regarding the duration of post‐operative pain. Also, in the research of Demiryilmaz et al, 12 the minimum duration of post‐operative pain was associated with the elliptical rotational flap and the maximum duration with primary repair may be due to stretching of tissue in primary repair surgery, which will increase the duration of post‐operative pain.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In research by Elsshazly et al, 20 the post‐operative pain in the LIMBERG flap procedure was significantly less than the excision and primary closure procedure groups ( P ‐value<.001). However, in separate studies by Karaks et al, 9 Ozcan et al, 5 and Berthier et al, 13 there was no significant difference between groups regarding the duration of post‐operative pain. Also, in the research of Demiryilmaz et al, 12 the minimum duration of post‐operative pain was associated with the elliptical rotational flap and the maximum duration with primary repair may be due to stretching of tissue in primary repair surgery, which will increase the duration of post‐operative pain.…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown that a tension‐free suture via bilateral rotational flaps having a good vacuum effect at the button of the wound meant for drainage of blood from the bottom of the wound is a key to success of repair without recurrence 17 . However, in a study conducted by Ozcan et al, 5 recurrence was detected in a total of 11 (23.4%) patients. Primary midline closure exhibited long‐term recurrence up to 67.9% in research by Stauffer et al 19 In a systematic review by Berthier et al, 19 it was indicated that all studies have reported data on disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of high body mass index (BMI) and surgical site infection (SSI) on the rate of PSD recurrence is discussed controversially [ 8 , 21 , 22 , 25 , 26 , 27 , 28 ]. While topical gentamycin application lowers the rate of SSI, it does not improve the long-term rate of PSD recurrence [ 21 ].…”
Section: Introductionmentioning
confidence: 99%